The influence of transformational school leadership on teacher efficacy in Malaysian secondary school teachers - Teh, Pei Ling; Lope Pihie, Zaidatol Akmaliah; Asimirin, Soaib; Foo, Say Fooi (Macrothink Institute, 2015)
This study provides an insight of the relationship between principals’ transformational school leadership practices and teacher efficacy among Malaysian secondary school teachers. Data was gathered from teachers of secondary schools in the central region of Peninsular Malaysia. The self-administered questionnaires, totalling 160 copies were distributed to the respondents. Valid samples stood at 137 teachers, resulting in a response rate of 85.6 percent. The data was analysed using descriptive, correlation and multiple regression analyses to evaluate the relationship between transformational leadership practices and teacher efficacy. The analysis revealed a significant relationship between the dimensions in transformational school leadership and teacher efficacy. The findings concur with the studies done by Leithwood (1994) that there is a significant relationship between the dimensions of transformational school leadership practices and teacher efficacy. These findings are also in line with past research (Kristine & Hipp, 1997; Peagler, 2004; Ross, J. A, Gray, 2006) that the said transformational leadership contributes toward teachers’ self-efficacy. Therefore, this study strengthens the findings by engaging in similar relationship.